A multiband triangular antenna for wireless communication applications - Nagnath Biradar; Kishan Singh (Institute of Advanced Engineering and Science, 2023)
Modern technology has made it easier to perform many tasks, including data, voice, video, and short-range device-to-device communication. These characteristics operate at different frequencies. In order to realize compact electronic devices and give users ease of movement, the antenna should operate on various frequency bands. This paper discusses the design of quad band antenna operating from 2.1 to 2.6 GHz, 3.9 to 4.9 GHz, 5.1 to 6.3 GHz, and 7.4 to 11.2 GHz. The realization of multiband is achieved using slots as parasitic elements on the radiator. These slots alter the antenna's regular current flow by generating a local, out-of-phase current channel with the same amplitude. The presented antenna has an overall electrical dimension of 0.22×0.16×0.01 λ3 (λ is determined using the frequency of 2.1 GHz). The 1.6 mm thickness FR4 substrate serves as the development platform for the proposed multiband antenna. The antenna has good reflection coefficient (S11), voltage standing wave ratio (VSWR), radiation characteristics, anda peak gain of around 5.1 dB. The results show design usefulness for wireless applications and are consistent with the measured values.